Spraying - Frank Aston::::::photographer::: (1909)
Faculty and students operating insecticide sprayer in orchard; appears to be battery powered pump drawing solution from wooden barrel -- whole apparatus is on horse drawn 'flatbed'. Men wearing ties, vests, jackets while working. The same spraying apparatus is in image published in the Polytechnic J. (vol.4, no. 8, May 1909). Spraying insecticides is listed in the description of the class in Horticulture, 1908-09 Catalog.